Paleoseismology of the Marquesado-La Rinconada thrust system, Eastern Precordillera of Argentina - Rockwell, Thomas K.; Costa, Carlos H.; Meigs, Andrew J.; Ragona, Daniel; Owen, Lewis A.; Murari, Madhav Krishna; Masana, Eulalia; Richard, Andrés D. (Frontiers in Earth Science, 2022)
Excavated trenches at two sites across the Marquesado-Rinconada fault system along the eastern Precordilleran front south of San Juan, Argentina, reveal the earthquake history of this rapidly urbanizing region. Interpretation of earthquakes is based on both the generation of colluvial wedges and upward fault terminations as well as folding events in fine-grained alluvium ponded behind upslope-facing fault scarps. The ages of the past five interpreted earthquakes at the Loma Negra site are: E1 at 2.8±2.8 ka, E2 at 7.1±1.5 ka, E3 at 9.6±1.3 ka, E4 at 14.4±2.1 ka, and E5 at 17.2±3.1 ka. At the Jejene sites, we document event ages of 2.7+0.1 ka, 3.9+0.55 ka, 5.9+1.3 ka and 11.4+4 ka. These observations indicate that the recurrence interval along the Marquesado=La Rinconada fault zone average several thousand years. The inferred displacements at the Jejenes site are about 1.1 m for E1, E3 and E4 and 2.1 m for event E2 whereas the displacements at Loma Negra averaged about a meter, but the most recent event displays less slip. Notably, the older events seem to have been larger and emergent whereas the youngest event appear to have been smaller and blind in the ponded sediment; this may partially explain the poor expression of classic colluvial wedges associated with some events. Despite the fact that active secondary surface faulting has an uncertain relationship with the primary seismic sources at depth in the crust, past and future events of Mw ~7.5 are consistent with the length scale of active deformation, the ~1 to 2 m slip per event scale of these secondary ruptures, and the size of historical earthquakes.